Control of Parallel Inverters in a Microgrid - Mr. Aissa SEGHIER; Mr. Ali BEDJ; Atallah BENALIA (AMAR TELIDJI UNIVERSITY OF LAGHOUAT.FACULTY OF TECHNOLOGY.DEPARTMENT OF ELECTROTECHNIC, 2022)
A worldwide shift towards more sustainable types of energies is being led by researchers worldwide, and the introduction of microgrids to integrate those types of energies is becoming more needful. This dissertation interests to the control of parallel inverters. The control is hierarchical in the sense that it should be carried out upon several levels, starting from the controlling of each inverter in voltage or current, then ensuring the power sharing between them using techniques like Master/Slave control and Droop control and finally implementing a voltage amplitude and frequency restoration for the Droop control method.
Option : Automatic and systems